Chemically strengthened glass and glass sidewalls using the same

JP2026165484APending Publication Date: 2026-10-14ASAHI BUILDING WALL +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057892
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、耐飛び石性及び耐熱性に特に優れた化学強化ガラスを得ることができ、特にDOLを12μmとすればさらに良好な耐飛び石性と厳しい条件での耐熱性も備えることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165484000004
    Figure 2026165484000004
  • Figure 2026165484000001
    Figure 2026165484000001
  • Figure 2026165484000002
    Figure 2026165484000002
Patent Text Reader

Abstract

This invention provides chemically strengthened glass and glass sidewalls made therefrom, which are particularly excellent in resistance to flying debris and heat, making them suitable for use as side walls for roads and railway tracks. [Solution] The chemically strengthened glass 1 according to the present invention has a glass plate 2 including a surface compression layer 3 formed on its surface and an internal tension layer 4 formed inside thereof, and has a compressive stress value (CS (MPa)) which is the same as the sum of stresses applied to the internal tension layer and is the maximum compression generated on the surface, the glass plate 2 has a depth DOL (μm) which is the depth at which CS is zero, the stress profile (CS / DOL) represented by CS and DOL is 11 or more and 59 or less, and DOL is 11 μm or more and 45 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to chemically strengthened glass that is excellent in stone-chip resistance and heat resistance and is suitable as a side wall for roads or railways, and a glass side wall using the same.

Background Art

[0002] Chemically strengthened glass is known as a type of tempered glass free from spontaneous breakage and tempering strain. Chemically strengthened glass is produced by immersing float glass in a potassium salt (potassium nitrate, potassium sulfate, potassium bisulfate, potassium carbonate, potassium bicarbonate, potassium chloride, etc.) solution, replacing sodium ions present inside the glass with potassium ions having a larger ionic radius than sodium ions, and forming an extremely thin compressive stress layer on the glass surface to increase the strength of the tempered glass.

[0003] With this tempering method, the glass surface forms a compressive stress layer, resulting in extremely high surface strength of the glass. For example, the surface compressive stress of ordinary air-cooled tempered glass is about 100 MPa, while that of chemically strengthened glass is about 600 MPa, though it varies depending on the production method. In addition, since the tensile stress inside the glass is small, spontaneous breakage is unlikely to occur, and the glass is characterized by good cutting workability. Furthermore, since it is produced by low-temperature treatment that does not heat the glass to its softening point, it has the same smoothness and transparency as float glass.

[0004] It is known to use such chemically strengthened glass as a panel installed on the roadside (see, for example, Patent Document 1). In Patent Document 1, by defining the compressive stress value (CS) and plate thickness of the chemically strengthened glass surface, it is intended to obtain a laminated glass and a translucent soundproof panel that are excellent in heat resistance and wind pressure resistance.

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Summary of the Invention

[0006] However, considering resistance to flying debris, it is necessary to increase the DOL (Depth of Compression) which indicates the depth from the glass surface to the compressive stress layer in order to prevent a decrease in the strength of the glass even if the glass surface is scratched. In particular, when used as a side wall for roads or railway tracks, flying debris can occur frequently, so it is necessary to set the DOL with resistance to flying debris in mind. Furthermore, heat resistance can be improved by introducing compressive stress to the surface, which cancels out the tensile stress generated by thermal expansion. Setting the CS (Critical Stress) is important in this regard. When used as a side wall for roads or railway tracks, this heat resistance must also be considered in order to prevent fire from spreading outward in the event of a fire. Therefore, when applying chemically strengthened glass as a side wall for roads or railway tracks, it is necessary to set the CS and DOL considering both resistance to flying debris and heat resistance.

[0007] The present invention takes into consideration the above-mentioned prior art and aims to provide chemically strengthened glass and glass sidewalls using the same, which are particularly excellent in resistance to flying stones and heat resistance and are suitable for use as side walls of roads and railway tracks. [Means for solving the problem]

[0008] To achieve the above objective, the present invention provides a chemically strengthened glass comprising a glass plate including a surface compression layer formed on its surface and an internal tension layer formed inside thereof, having a compressive stress value (CS (MPa)) which is the sum of the stresses applied to the internal tension layer and is the maximum compression generated on the surface, having a depth DOL (μm) to which the CS becomes zero, having a stress profile (CS / DOL) represented by the CS and DOL of 11 to 59, and having a DOL of 11 μm to 45 μm.

[0009] Preferably, the DOL is 12.8 μm or more and 45 μm or less.

[0010] Preferably, the plate thickness is 2.5 mm or more.

[0011] Furthermore, the present invention provides a glass side wall made of chemically strengthened glass that can be used as a side wall along a road or railway line.

[0012] Preferably, the structure comprises a passage-side glass plate made of chemically strengthened glass, positioned on the inside of the road or railway tracks, and a private-land-side glass plate made of chemically strengthened glass, which is attached to the outside of the passage-side glass plate via an adhesive layer, wherein the thickness of the passage-side glass plate is equal to or greater than the thickness of the private-land-side glass plate, and the combined thickness of the passage-side glass plate and the private-land-side glass plate is 6 mm or more. [Effects of the Invention]

[0013] According to the present invention, chemically strengthened glass with particularly excellent resistance to flying debris and heat can be obtained, and if the DOL is set to 12 μm, even better resistance to flying debris and heat resistance under harsh conditions can be achieved.

[0014] Furthermore, by making the plate thickness 2.5 mm or more, it is possible to obtain chemically strengthened glass with excellent wind pressure resistance, and if it is 4 mm or more, it can also be provided with sound insulation.

[0015] Furthermore, the present invention is suitable for use as a glass side wall along a road or railway line, as such side walls require particular resistance to flying debris and heat.

[0016] Furthermore, by using laminated glass made of chemically strengthened glass for the glass sidewalls, making the thickness of the glass panel on the walkway side greater than or equal to the thickness of the glass panel on the private property side, and making the total thickness of this laminated glass 6 mm or more, the glass sidewalls can also be provided with the additional wind pressure resistance, sound insulation, and impact resistance required. [Brief explanation of the drawing]

[0017] [Figure 1] This is a schematic diagram visualizing the various stresses acting on chemically strengthened glass. [Modes for carrying out the invention]

[0018] First, let's explain the stress on the chemically strengthened glass 1, referring to Figure 1. The glass plate 2 that forms the chemically strengthened glass 1 has a surface compression layer 3 on its surface. Inside this surface compression layer 3 is an internal tension layer 4. The surface compression layer 3 is subjected to compressive stress, and the maximum compression occurring on the surface among the compressive stress values ​​that have the same total sum as the total internal stress (represented by the area of ​​B in Figure 1) (represented by the area of ​​A in Figure 1) is called CS. The thickness of the glass plate 2 is denoted as t.

[0019] This CS is introduced by chemical strengthening treatment through ion exchange from the glass surface, so it gradually decreases from the glass surface towards the interior of the glass plate 2. The depth at which CS becomes zero is called DOL. The maximum value of tensile stress in the internal tensile layer 4 is called CT. When a reference line S is set as shown in Figure 1, the stress at that point is such that the surface compression layer 3 is subjected to compressive stress consisting of CS and DOL, and the internal tensile layer 4 is subjected to tensile stress consisting of CT.

[0020] When each stress is visualized in this way, the sum of compressive stresses and the sum of tensile stresses in chemically strengthened glass 1 are balanced (they are the same value). In other words, in Figure 1, chemically strengthened glass 1 is formed when the sum of the areas shown in A and the area shown in B are the same. A is approximately a triangle, and its area is expressed as (CS × DOL) / 2. B is approximately a rectangle, and its area is expressed as (t-2DOL) × CT. However, since DOL is on the order of tens of micrometers compared to the thickness of the glass plate 2, the size of DOL does not have much effect on t. In that case, the area of ​​B is expressed as t × CT.

[0021] When the sum of these areas is equal, 2×A=B holds, leading to CS×DOL=t×CT (Equation 1). When CT is large (for example, exceeding 4.5 MPa), spontaneous breakage tends to occur, and a slight impact may cause cracking due to flaws or risk delayed fracture. Therefore, setting CT to a large value should be avoided. CT is preferably 4.5 MPa or less. Increasing the plate thickness of the glass plate body 2 physically enlarges the glass plate body 2 and is also affected by its weight, so priority should first be given to reducing CT by varying CS and DOL. Accordingly, as shown in Equation 1, to keep CT at a small value, the value of CS or DOL may be reduced.

[0022] Increasing DOL enhances the resistance to flaws generated in the glass plate body 2, so the allowable stress also increases. The allowable stress refers to the stress that is permitted under a certain safety factor, which is derived by conducting glass strength tests using a large number of test specimens, obtaining the safety factor from the strength variation (standard deviation), and using it for glass strength calculation. On the other hand, it is known that increasing CS increases the allowable stress itself, but when DOL and t are constant, CT also becomes a large value, making spontaneous breakage, delayed fracture and the like more likely to occur. Further, to increase the allowable stress, increasing DOL to reduce strength variation is more efficient than increasing CS. Therefore, by increasing DOL while keeping CS at an appropriate value, the value of CT can be kept small, and a predetermined allowable stress can be obtained. In other words, it can be said that priority should first be placed on focusing on DOL.

[0023] Here, the stress profile (CS / DOL) was used as an indicator of what balance of CS and DOL settings would be effective. This is the slope of the hypotenuse of the triangle indicated by A in FIG. 1, and can also be referred to as the absolute value of the average slope of the stress profile from the surface of the glass plate body to the DOL. Since the average slope of the stress profile from the surface to the DOL is "CS / DOL (MPa / μm)", by increasing the DOL while keeping CS at an appropriate level, the average slope becomes a small value, CT is suppressed to a small value, the risk of the aforementioned spontaneous breakage and delayed fracture is eliminated, and a predetermined allowable stress can be secured.

[0024] The present invention was made in consideration of the above viewpoints, focusing on the optimal range of the stress profile and DOL, with emphasis on performance that is particularly suitable when used as a side wall disposed along a road or railway. Hereinafter, evaluations obtained by each test are shown.

[0025] <Stepping stone resistance, heat resistance> ·Stepping stone resistance evaluation Purpose: To confirm the presence or absence of breakage due to flying stones and the like from the vehicle body side of roads and railways. Test method: A 4.5 g SUS iron ball (nominal diameter 13 / 32 inch) was collided head-on at an impact velocity of 21.0 m / s (75.6 km / h) at 6 arbitrary positions on the glass plate body. Test results: A total of 3 glass plate bodies were used for the test. Cases where all positions (18 positions in total) were completely intact were marked as ○, cases where impact marks with no effect on strength were visually confirmed at several positions were marked as △, and cases where the glass plate body was cracked at one or more positions were marked as ×.

[0026] ·Heat resistance evaluation A Purpose: To confirm the fire resistance against fires originating from the vehicle body side of roads and railways. Test method: A propane gas type burner with a diameter of 10 mm was installed at a distance of 40 cm between the glass plate body and the burner port, and irradiation was performed for a total of 2 minutes. The thermal integral value of the flame temperature was set to 96000°C·seconds or more to reproduce a fire from a vehicle body or the like. Test results: Glass plates that did not burn, or that extinguished themselves within 20 minutes of ignition and did not fall off the road, were marked with a circle (○), and all others were marked with a cross (×).

[0027] • Heat resistance rating B Objective: To verify the fire resistance against fires originating from the vehicle body of roads and railways. This is a more rigorous test than Heat Resistance Rating A and is required in a safer environment. Test method: The heating conditions in the combustion experiment were carried out based on the standard heating temperature curve of ISO 834-1 (using a heating furnace). Test results: After a total of 4 minutes of heating, samples were marked with a ○ if the flame did not penetrate the glass plate during the combustion test, and with a × if the flame penetrated and spewed flames outwards.

[0028] The test results are shown in Table 1. Note that in Comparative Example 1 and Examples 1 through 8, the tests were conducted using single sheets of chemically strengthened glass.

[0029] [Table 1]

[0030] As is clear from Table 1, for stone chip resistance, which is particularly important when used as a side wall along a road, a DOL of 11 μm or higher is necessary. The upper limit of DOL was set at 45 μm, but it is thought that even higher values ​​would still be effective in terms of stone chip resistance. Within this DOL range, the stress profile considering stone chip resistance was between 11 and 59.

[0031] Here, in situations where a certain degree of resistance to flying stones is required and such strict heat resistance is not necessary, Example 1 can be applied. However, when used in situations that require more stringent conditions, the range shown in Examples 2 to 6 is preferable. In that sense, it is preferable that the lower limit of DOL be 12.8 μm or more, as shown in Example 2. That is, DOL is preferably 12.8 μm or more and 45 μm or less. In this case, the upper limit of the stress profile value will be 50.8 or less. That is, the stress profile value is preferably 11 or more and 50.8 or less.

[0032] This test shows that chemically strengthened glass with particularly excellent resistance to flying debris and heat can be obtained under the above conditions, and that if the DOL is set to 12 μm, even better resistance to flying debris and heat resistance under severe conditions can be achieved.

[0033] <Wind pressure resistance, sound insulation, impact resistance> • Wind pressure resistance evaluation Objective: To confirm that the glass panel will not be damaged by strong winds or other forces. Test method: Place the glass plate horizontally and apply a load equivalent to wind pressure of 3.0 kN / m above it. 2 It was loaded. Test results: Glass plates that did not break were marked with ○, and those that broke were marked with ×.

[0034] • Sound insulation evaluation Objective: To verify the sound insulation performance against noise generated from road and railway vehicles. Test method: Sound transmission loss was measured at each frequency, and the sound transmission loss at 400 Hz and 1000 Hz was evaluated in dB. Test results: Tests with a level of 25 dB or higher at 400 Hz and 30 dB or higher at 1000 Hz were marked with a circle (○), while all other tests were marked with a cross (×).

[0035] • Impact resistance evaluation Objective: To confirm the safety of private land in the event that cargo or other items fall from the side of a road or railway vehicle. Test Method: The glass plate was positioned so that its lower end was at a height of 1 m above the road surface. A 300 kg steel ball (with protrusions) was struck in a pendulum-like motion from a height of 95 cm vertically from the impact point at the center of the glass plate. The maximum weight of the scattered fragments (weight of the heaviest fragment) and the number of scattered fragments were measured. The shatter prevention rate was also calculated using the following formula. {Weight of glass plate (after breakage) / Weight of glass plate (before breakage)} × 100 Test results: Products with a maximum weight of 1.0 kg or less and a shatter prevention rate of 99.0% or higher were marked with a circle (○), and all others were marked with a cross (×).

[0036] The test results are shown in Table 2. Note that Comparative Example 2, Example 7, and Example 8 were all tested using chemically strengthened glass as a single sheet.

[0037] [Table 2]

[0038] As is clear from Table 2, plate thickness is an important factor for wind pressure resistance and sound insulation. In order to have wind pressure resistance in addition to the aforementioned resistance to flying stones and heat, as shown in Example 7, a total plate thickness of at least 2.5 mm is required at the lower limit of CS of 350 MPa where impact resistance is obtained. Furthermore, as shown in Example 8, if sound insulation is also considered, a total plate thickness of 4 mm or more is preferable. As long as the total plate thickness is above these levels, the performance in terms of wind pressure resistance and sound insulation will not decrease.

[0039] Here, when using the chemically strengthened glass according to the present invention as a glass side wall for roads or railway tracks, it is preferable to form two sheets of chemically strengthened glass as laminated glass. In this case, the laminated glass is formed by a walkway-side glass plate made of chemically strengthened glass, which is positioned on the inside relative to the road or railway track, and a private-land-side glass plate made of chemically strengthened glass, which is attached to the outside of the walkway-side glass plate via an adhesive layer. Using this laminated glass, the above-mentioned wind pressure resistance, sound insulation, and impact resistance tests were conducted. The test results are shown in Table 3.

[0040] [Table 3]

[0041] As is clear from Table 3, laminated glass provides impact resistance that could not be obtained with single-pane glass. However, impact resistance cannot be obtained with all laminated glass. For example, as shown in Comparative Example 4, if the thickness of the glass panel on the walkway side is thinner than the thickness of the glass panel on the private property side, impact resistance cannot be obtained. Therefore, it is preferable that the thickness of the glass panel on the walkway side is equal to or greater than the thickness of the glass panel on the private property side. It can be seen that a combined thickness of 6 mm or more for the glass panels on the walkway side and the private property side is sufficient. Note that the same CS was used for both the walkway side and the private property side in each example and comparative example.

[0042] Furthermore, as shown in Comparative Example 3, impact resistance cannot be obtained if the CS is below 350 MPa. Therefore, it is preferable that the CS be 350 MPa or higher. The fact that the CS is 350 MPa is also present in Examples 1 to 8 shown in Tables 1 and 2. However, as shown in Comparative Example 1, if the CS is 700 MPa, the resistance to flying stones is lost, so it can be said that it is preferable that the CS be between 350 MPa and 670 MPa.

[0043] From the above, considering wind pressure resistance, sound insulation, and impact resistance, it is important that the thickness of the glass panel on the walkway side is equal to or greater than the thickness of the glass panel on the private property side, and that the combined thickness of the glass panels on the walkway side and the private property side is 6 mm or more. Furthermore, as can be seen from Table 3, it is also important that the thickness of the glass panel on the private property side is 4 mm or less. This is because in Comparative Example 4, the thickness of the glass panel on the private property side is 5 mm, resulting in insufficient impact resistance. [Explanation of Symbols]

[0044] 1: Chemically strengthened glass, 2: Glass plate, 3: Surface compression layer, 4: Internal tension layer

Claims

1. The glass plate comprises a surface compression layer formed on the surface and an internal tension layer formed inside thereof, The surface compression layer has a compressive stress value (CS (MPa)) which is the maximum compression generated on the surface and is the same sum as the total stress applied to the internal tension layer. The glass plate has a depth of DOL (μm) where the CS is zero. The stress profile (CS / DOL) represented by CS and DOL is 11 or more and 59 or less. A chemically strengthened glass characterized in that the DOL is 11 μm or more and 45 μm or less.

2. The chemically strengthened glass according to claim 1, characterized in that the DOL is 12.8 μm or more and 45 μm or less.

3. The chemically strengthened glass according to claim 1, characterized in that the plate thickness is 2.5 mm or more.

4. A glass side wall made of chemically strengthened glass according to any one of claims 1 to 3, characterized in that it is used as a side wall arranged along a road or railway line.

5. A passageway-side glass panel made of chemically strengthened glass, which is positioned on the inside of the road or railway tracks, The glass panel on the passageway side is attached to the outside of the passageway side via an adhesive layer and comprises a glass panel on the private property side made of the aforementioned chemically strengthened glass, The thickness of the glass panel on the passageway side is equal to or greater than the thickness of the glass panel on the private property side. The glass side wall according to claim 4, characterized in that the total thickness of the glass plate on the passageway side and the glass plate on the private property side is 6 mm or more.

Citation Information

Patent Citations

  • Antenna structure

    JP1984021103A